2008
DOI: 10.1080/15299730802139311
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation in Major Depressive Disorder: A Pilot Study

Abstract: The principal objective of this study was to evaluate the occurrence of various dissociative phenomena in patients with major depressive disorder (MDD) and their possible implications in manifestation and course of depression. We administered the Dissociative Experiences Scale (DES) and a self-questionnaire of life events to 27 patients with MDD and to 40 healthy participants in order to collect information on traumatic events. Patients who scored >or= 20 on the DES were also assessed to determine the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The redundancy between negative emotions and dissociation is explained by the finding that depressed individuals tend to dissociate as a method of coping. 41,42 There are several limitations present in this study. First, due to the self-selected nature of the recruitment, the respondents were overwhelmingly male, and accordingly, these findings may not generalize to female Texas Hold'em players.…”
Section: Discussionmentioning
confidence: 83%
“…The redundancy between negative emotions and dissociation is explained by the finding that depressed individuals tend to dissociate as a method of coping. 41,42 There are several limitations present in this study. First, due to the self-selected nature of the recruitment, the respondents were overwhelmingly male, and accordingly, these findings may not generalize to female Texas Hold'em players.…”
Section: Discussionmentioning
confidence: 83%
“…Dissociative symptoms are highly related to depression and suicidality (Foote, Smolin, Neft, & Lipschitz, 2008;Maaranen et al, 2005) and to substance use and borderline traits in youth (Chabrol, Rodgers, & Ducongé, 2005). Dissociation is generally regarded as a defense against painful affects, including depressive feelings (e.g., Molina-Serrano, Linotte, Amat, Souery, & Barreto, 2008). Among adolescents, substance use has been put forward as an important risk factor for suicidal ideation and behavior (Beautrais, 2000;Fergusson, Beautrais, & Horwood, 2003).…”
mentioning
confidence: 98%
“…It has been suggested that the presence of PD and concomitant neurological changes may increase an individual’s risk of PTSD or depression (Hodgson & Webster, 2011; Inslicht et al, 2010; Johnson et al, 2001; Marmar et al, 1996; Ozer, Best, Lipsey, & Weiss, 2003). However, these relationships are inconsistently shown, possibly due to risk factors that modify the relationship between PD, PTSD, and depression (Molina-Serrano et al, 2008). Prior trauma may be one of these risk factors.…”
mentioning
confidence: 99%